Decreasing of placental progesterone induced blocking factor expression and spiral artery remodeling disturbance in mice preeclampsia model - Manggala Pasca Wardhana (2015)
Introduction Preeclampsia is a major cause of morbidity and mortality in our developing country. The biggest obstacle in the high prevalence of preeclampsia and its management is due to lack of knowledge in preeclampsia pathologic mechanism. Progesterone is an important pregnancy hormone that has immunomodulatory effect by inducing progesterone induced blocking factor (PIBF) release, due to binding of progesterone with its receptor in lymphocyte. PIBF inhibits cytolytic NK cells activity and inducing T-helper 2 cytokine dominant while on contrary, preeclampsia has a condition of T-helper 1 cytokine dominant and increase of NK cells cytolytic activity. This was the first study to evaluated PIBF expression directly on the placenta when the pathogenesis of preeclampsia occurred after completion of vascular remodeling in animal models. Objective The objectives of this study were to compare placental PIBF expression, spiral artery wall thickness as characteristic of vascular remodeling disturbance and investigated correlation between both in mice preeclampsia model. Methods This experimental study used 32 pregnant mus musculus mice and randomly divided to normal group and preeclampsia model group. Our preeclampsia model was created by injecting anti-Qa2 (anti HLA-G) 10 ng from 1st until 4th day of pregnancy, to reduced HLA-G expression. Termination of both groups were performed after completion of spiral artery remodeling in mice by day 16th of pregnancy followed by immunohistochemistry examination for PIBF expression using immunoreactive score and spiral artery wall thickness measurement. Ethical clearance was taken from Medical Veterinary Faculty ethics commission. Difference and correlation were analysed using SPSS 20. Probability values <0.05 were considered statistically significant. Result In the result, PIBF were expressed in trophoblast, decidual and lymphocyte cells in placental tissue. The placental PIBF expression on preeclampsia model (2.01 ± 1.14) was significantly reduced (p ± 0.01) compared with control (3.99 ± 2.53). There was a significant increase of spiral artery wall thickness (p ± 0.001) in preeclampsia model (20.70 ± 5.93 micrometers) compared with control (9.98 ± 3.36 micrometers). There was a significant association (p ± 0.001) with negative correlation (rho/Pearson correlation = −0.623) between placental PIBF expression and the spiral artery wall thickness. Conclusion We concluded a decreased expression of placental PIBF and the increase of spiral artery wall thickness as a characteristic of spiral artery remodeling disturbance in mice model of preeclampsia, with negative correlation between placental PIBF expression and spiral artery wall thickness.